STUDI PEMANFAATAN GAS BUANG UNTUK REFRIGERASI SISTEM ABSORPSI BAGI PENYIMPAN DINGIN INDUSTRI PERIKANAN - , Teguh Kristianto; , Ir. Samsul Kamal, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a country rich in fish , one of the main fish in south of the Java island is Skipjack. Once captured and dead, fish is a kind of food that easily damage if not properly preserved. One method of preserving fish is keep it in cold conditions between 80C to 00C . The fishermen in Sadeng , Girisubo , Gunung Kidul , Yogyakarta are still use ice cube to preserving fish on board. Diesel engineexhaust gas containing about 30% of the heat of combustion. Exhaust gas temperature is between 600 â 7000C in the exhaust manifold . In this research, hot gas utilized for energy source of absorption refrigeration system to preserve Skipjack . This research uses an absorption refrigeration unit UPO Finland . Heat energy generated from the combustion of LPG . Hot gas mass flow rate are varied 1.5 kg / hour , 1.8 kg / hour , and 2.1 kg / hour . The amount of fish in this research is 4 kilogram. The results obtained from this research is cooling capacity proportional to the mass flow rate of hot gas . In this reearch, the best results is obtained for hot gas mass flow rate of 2.1 kg / hour. At that point recorded that evaporator temperature reach -14.80C, the air temperature inside the refrigerator is 1.90C , and the Skipjack temperature is 50C